ANALYSIS OF GROSS PROFIT MARGIN AND QUICK RATIO ON SHARE PRICES IN PT. HUTAMA KARYA (PERSERO) - fatmawati fatmawati; M Rimawan (JASS (Journal of Accounting for Sustainable Society), 2022)
This study aims to analyze gross profit margin (GPM) and quick ratio (QR) against the share price in PT. Hutamakarya (persero), in this study conducted an analysis of financial statements using financial ratios as a measurement tool, such as gross profit margin (GPM) and quick ratio (QR). This research includes a type of associative research that is a research formulation that is questioning, the relationship between two or more variables, the population in this study is the data of financial statements for 20 Years from 2000-2019 at PT Hutama karya (persero). the samples used in this study are financial statements for the last 10 years, starting from 2010-2019, sampling techniques with purposive sampling. Data analysis method using multiple linear regression analysis with testing the test hypothesis t. from the results of the study showed that gross profit margin (GPM) has no significant effect on the share price, quick ratio (QR) has no significant effect on the share price, so it can be concluded that gross profit margin (GPM) and quick ratio (QR) both have no effect on the share price in PT. Hutama karya (persero)